Analisis Tingkat Kesejahteraan Petani Kedelai Dengan Menggunakan Pendekatan Nilai Tukar Petani (Ntp) Dan Nilai Tukar Pendapatan Rumah Tangga Petani (Ntprp) - Rizkya Adzhura Puteri Setiawan; Trisna Insan Noor; Lies Sulistyowati; Iwan Setiawan (JURNAL AGRIBISNIS TERPADU, 2019)
Soybean is one of food crops in order that become attention from the government because the request of the soybean  as a raw material keep rising throughout the day. Seeing this condition the government introduced a program to increase soybean production. The Jatiwaras Village, Jatiwaras Sub District, Tasikmalaya District become one of the center of soybean development. This study attempts to analyzed levels of prosperity and poverty in soybean farmers at the Village of Jatiwaras. The research uses exchange farmers rate and exchange household income. The results of research to analyses the prosperity of soybean farmers in the Jatiwaras Village using NTP and NTPRP shows that the prosperity of farmers were still low at category value of NTP is 61,18 and value of NTPRP is 0,62 it is because that the income the receive from soybean farming is not able to satisfy the needs of households soybean farmers.